B.R.M.G. SAYIDIN MALIKUL KUSNO: PELOPOR PENDIDIKAN MASYARAKAT - Hermanu Joebagyo (LPMPP Universitas Negeri Yogyakarta, 2009)
This article analyzes the existence of Madrasah Mambaul Ulum, HIS Kasatryan and HIS Pamardi Putri in the political constellation of the movements in 1920s.These educational institutions were established in the area of the Kasunanan Palace. Madrasah Mambaul Ulum consisted of elementary school, junior high school and senior high school, catering for children of abdi dalem (servants in the palace) and those of lay people. On the other hand, HIS Kasatryan and HIS Pamardi Putri were elementary schools for children of lower aristocrats. The founders of the institutions gave freedom to the managers to make decisions concerning education (school-based management) in terms of the curriculum, teachers, learning materials, learning strategies, and evaluation system. Even society members were allowed to take part in the implementation (community-based education). The local contents, the Javanese culture and Islam were the subjects that guided the students ethics and moral so that they developed as individuals who were responsible and just and capable of protecting their fellow people. Keywords: Madarasah Mambaul Ulum, HIS Kasatryan, HIS Pamardi Putri, Javanese culture, Islam